2021
DOI: 10.1038/s41598-021-83860-3
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing laser speckle reduction by decreasing the pitch of a chiral nematic liquid crystal diffuser

Abstract: The artefact known as speckle can plague numerous imaging applications where the narrow linewidth of laser light is required, which includes laser projection and medical imaging. Here, we report on the use of thin-film chiral nematic liquid crystal (LC) devices that can be used to mitigate the influence of speckle when subjected to an applied electric field. Results are presented which show that the speckle contrast (a quantitative measure of the presence of speckle) can be significantly reduced by decreasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…At higher field amplitudes the LC transforms to a homeotropic nematic LC alignment, so EHDI ceases and no speckle reduction is observed in this state. [ 18 ] Figure 3d is an example of a high‐resolution scan conducted to find the precise field conditions at which the speckle contrast was minimized; in this case, the results show that the lowest speckle contrast was observed for an amplitude of E = 15.3 V μm −1 and a frequency of f = 38 Hz. This field amplitude is quite large because of the relatively short pitch (<400 nm) of the chiral nematic LC used (hence a large unwinding field), and the frequency optimizes turbulence in the conductive EHDI regime while ensuring that an associated flicker is not visible to the human eye.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At higher field amplitudes the LC transforms to a homeotropic nematic LC alignment, so EHDI ceases and no speckle reduction is observed in this state. [ 18 ] Figure 3d is an example of a high‐resolution scan conducted to find the precise field conditions at which the speckle contrast was minimized; in this case, the results show that the lowest speckle contrast was observed for an amplitude of E = 15.3 V μm −1 and a frequency of f = 38 Hz. This field amplitude is quite large because of the relatively short pitch (<400 nm) of the chiral nematic LC used (hence a large unwinding field), and the frequency optimizes turbulence in the conductive EHDI regime while ensuring that an associated flicker is not visible to the human eye.…”
Section: Resultsmentioning
confidence: 99%
“…The pitch was chosen based on the findings of previous work. [ 18 ] The mixtures were placed on a hot stage with a magnetic stirrer and were heated up to 5 °C above the clearing point for a period of 24 h. After thermal mixing, the LC mixture was then filled via capillary action into commercially available INSTEC LC2 cells that have a nominal cell gap of d = 20.0 μm. Indium tin oxide (ITO) coatings of 23 nm on the inner substrates served as transparent electrodes and were patterned onto the inner sides of the glass substrates to create an active region of 5 mm × 5 mm at the centre of the cell.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[3,4] Some passive techniques have been utilized to reduce the coherence of illumination lasing through moving components and time integration [5,6] to suppress the coherent noise. [7,8] They limit the time resolution of the imaging DOI: 10.1002/apxr.202200054 system. To meet the requirements of real-time display, the active methods of lowering lasing coherent are required for the next generation of lasing display.…”
Section: Introductionmentioning
confidence: 99%
“…Liquid crystals (LCs) have been widely used in the display field because of their excellent electro-optical properties and have become ideal fillers for static diffusers. Some research groups have reported studies on speckle reduction by LCs [ [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] ] because LC molecules have unique birefringence properties and can be modulated by an electric field. LCs are typically used for speckle reduction in the form of polymer LC composites, in which dynamic transition between the scattering and transparent states can be achieved by voltage control.…”
Section: Introductionmentioning
confidence: 99%